Adaptation to climate change and promotion of environmental sustainability in Zimbabwe’s semi-arid areas: the case of Ngundu ward in Chivi: paper presented at a conference held on the 14th-16th July 2015, Elephant Hills Resort, Victoria Fallls, Zimbabwe - Nciizah, Elinah (Midlands State University, 2016)
Theme: 1st International Research Conference On Driving Socio-Economic Development Through Value Addition And Sustainable Use Of Resources